A Multiancestry Sex-Stratified Genome-Wide Association Study of Spontaneous Clearance of Hepatitis C Virus. (29th October 2020) - Vergara, Candelaria; Valencia, Ana; Thio, Chloe L; Goedert, James J; Mangia, Alessandra; Piazzolla, Valeria; Johnson, Eric; Kral, Alex H; O'Brien, Thomas R; Mehta, Shruti H; Kirk, Gregory D; Kim, Arthur Y; et al.
Abstract: Background: Spontaneous clearance of acute hepatitis C virus (HCV) infection is more common in women than in men, independent of known risk factors. Methods: To identify sex-specific genetic loci, we studied 4423 HCV-infected individuals (2903 male, 1520 female) of European, African, and Hispanic ancestry. We performed autosomal, and X chromosome sex-stratified and combined association analyses in each ancestry group. Results: A male-specific region near the adenosine diphosphate–ribosylation factor–like 5B ( ARL5B ) gene was identified. Individuals with the C allele of rs76398191 were about 30% more likely to have chronic HCV infection than individuals with the T allele (OR, 0.69; P = 1.98 × 10 −07 ), and this was not seen in females. The ARL5B gene encodes an interferon-stimulated gene that inhibits immune response to double-stranded RNA viruses. We also identified suggestive associations near septin 6 and ribosomal protein L39 genes on the X chromosome. In box sexes, allele G of rs12852885 was associated with a 40% increase in HCV clearance compared with the A allele (OR, 1.4; P = 2.46 × 10 −06 ). Septin 6 facilitates HCV replication via interaction with the HCV NS5b protein, and ribosomal protein L39 acts as an HCV core interactor. Conclusions: These novel gene associations support differential mechanisms of HCV clearance between the sexes and provide biological targets for treatment or vaccine development. Abstract : Using sex-stratified genome-wide association analyses we identified a male-specific association of spontaneous clearance of hepatitis C virus and markers near adenosine diphosphate–ribosylation factor–like 5B gene in chromosome 10 and suggestive associations near septin 6 and ribosomal protein L39 genes on the X chromosome with effects in both sexes.